Crimes licitatórios à luz da Teoria do Bem Jurídico Penal - Zan, Marcela Albuquerque (2016)
This work, without pretending to exhaust the subject, aims to offer a systematic examination pertaining to bidding crimes to the Theory of Criminal Law well. Separately examining the historical evolution of the legal asset, its concept and functions, we consecrate its importance in the social and democratic rule of law. It is essential institute to give empirical basis to the Criminal Law and linking this with the reality of social values. Extending the study to the Federal Constitution, as the highest expression of the guiding principles of the legal system, the legal right to have her endorsement own dignity. In this context, the principle of minimum intervention determines that only the most expensive legal interests of individual life and society on a constitutional reading, can be part of the fragment will be safeguarded by criminal law and only the conduct that most violate these value will be criminalized . Still, it should be done considering the need of the criminal front protects the failure of other branches of law. On the study of the principle of proportionality, especially in its aspect of sealing the poor protection, criminal law and the institute is duty of the State with a view to effective action. It s essential to analyze the criminalization warrants, the universal legal values and legitimacy of abstract danger crime for the formation of a Criminal Law concatenated with the fundamentals and objectives of the Federative Republic of Brazil. Application of the Theory of Criminal Legal Values is a safe basis for critical analysis of public bidding crimes. Public bidding process is not a mere administrative procedure to choose the best contract, but is instrument for achieving social rights. So we try to show that the legal interest of specific offenses for your protection is not only the public purse, but the administrative probity and public interest of good administration. Under this test, if the criminal value has dignity and necessity of penal treatment, must be effectively guarded. The criminal policy should be optimized so that the constitutional mandate is fulfilled properly. It is from this understanding that will be assessing the public bidding crimes